Political Conflict Among Factions: A Criticism on Veronica Roth's Novel Divergent (2011) - Prasgiyardi, Harnanto; , Dr. Phil. Dewi Candraningrum, M.Ed; , Titis Setyabudi, S.S, M.Hum (2016)
The major problem in this research is describing the political conflict among factions whichis reflected in Veronica Roth's novelDivergent. The research consists of an objective: analyzing the novel based on Marxist Criticism. The researcher employs qualitative method. The object of the study is Divergent novel by Veronica Roth which is published in 2011. The data sources consist of primary data source and secondary data source. The primary data source is the text of Divergent by Veronica Roth, published by Harper Collins and the secondary data sources are references or materials related to study which are taken from books, websites, and other matters that support this analysis. The method of collecting data in this research is library research by summarizing, paraphrasing, and documenting the data. The technique of data analysis is descriptive analysis. The result of this research shows that Roth generally wants to describe the social classes in the post-apocalyptic Chicago. Divergent also shows the conflict between factions that fight to get the authority of the council.